Jumbo Flying Squid Distribution within Anticyclonic Eddies under Anomalous Climatic Conditions - Pengchao Jin; Jiangtao Fan; Xiaoci Wu; Yanling Du; Wei Yu (Ecosystem Health and Sustainability, 2024)
Anticyclonic eddies are widely distributed off Peru, producing obvious effects on climate-environment-sensitive jumbo flying squid Dosidicus gigas. However, how the habitat of D. gigas changes within anticyclonic eddies during El Niño events is still unknown. Therefore, this study constructed a habitat model with different weights and screened the optimal performance model using fishery data from September to December during 2015 to 2019, as well as vertical water temperature data (sea surface temperature and 50 m water depth temperature) and surface chlorophyll concentration data (Chl-a). Then, combined with the eddy tracking dataset, the differences in the variation of resource abundance and habitat of D. gigas within the anticyclonic eddy between the 2015 El Niño year and the 2019 normal year were further comparatively analyzed based on the optimal habitat model. Compared with the normal year of 2019, the 2015 El Niño event occurred with a lower intensity of eddy activity, and both temperature in the fishing ground and near-surface sea water temperature within the anticyclonic eddy became warmer, with a small decrease in Chl-a; the percentage of suitable near-surface water temperature within the anticyclonic eddies decreased significantly, and suitable Chl-a decreased slightly; the suitable habitat for D. gigas was reduced dramatically, which was unfavorable to D. gigas survival. Our finding suggested that that anomalous climatic events can have an impact on eddy strength, as well as on the suitable environment and habitat within the anticyclonic eddies, resulting in variations in the abundance of D. gigas.